Faktor-Faktor Yang Mempengaruhi Penghindaran Pajak Manufaktur di Indonesia - Paramita Rari Gunita; Rachmawati Meita Oktaviani (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of this study was to identify the variables that affect tax avoidance, the dependent variable. Leverage, profitability, and company size are employed as independent variables. For the 2018–2021 period, this analysis uses secondary data gathered from yearly reports obtained from the Indonesian Stock Exchange. Purposive sampling was used to collect 96 samples from 24 companies over a 4-year period, from 2018 to 2021. Eviews 10 software was used to process this research. The Chow test, Hausman test, and Lagrange multiplier test were the techniques employed. The conclusion reached is that tax evasion is influenced by leverage. While company size and profitability have no bearing on tax avoidance.